Efektivitas Flashcard Game Terhadap Minat dan Pengetahuan dalam Menjaga Kesehatan Gigi pada Anak Sekolah Dasar - Alfansa Fath Syaira; Ardhiles Wahyu Kurniawan; Heny Nurmayunita (Universitas Malahayati, 2026)
ABSTRACT Dental health problems in elementary school children are still commonly found, mainly due to low interest and knowledge in maintaining dental hygiene. The purpose of this study was to analyze the effectiveness of flashcard games on interest and knowledge in maintaining dental health among fourth-grade students at Islamic Global School Malang. This study was a quantitative comparative analysis using a one-group pretest-posttest design. The research population consisted of 100 students, with a sample of 80 respondents selected using simple random sampling. The instrument used was a questionnaire on interest and knowledge that had undergone validity and reliability tests. Statistical analysis used the Paired t-test for the interest variable and the Wilcoxon test for the knowledge variable with a significance level of α = 0.05. The pretest results showed that most respondents were in the moderate interest (78.8%) and moderate knowledge (62.5%) categories. After being given the flashcard game, almost all respondents were in the good interest (61.3%) and good knowledge (78.8%) categories. A p-value 0.001 in the Wilcoxon test and p = 0.000 in the Paired T-test indicate a difference before and after the intervention. The conclusion of this study is that flashcard games are effective in increasing the interest and knowledge of elementary school students in maintaining dental health. Keywords: Dentah Health, Elementary school, Flash Card, Game, Interest, Knowledge. ABSTRAK Masalah kesehatan gigi pada anak sekolah dasar masih sering ditemukan, terutama akibat rendahnya minat dan pengetahuan dalam merawat kebersihan gigi. Tujuan penelitian ini adalah untuk menganalisis efektivitas flashcard game terhadap minat dan pengetahuan dalam menjaga kesehatan gigi pada siswa kelas IV SD Islamic Global School Malang. Penelitian ini merupakan kuantitatif analitik komparatif dengan pendekatan one group pretest–posttest design. Populasi penelitian berjumlah 100 siswa, dengan sampel 80 responden yang dipilih menggunakan teknik simple random sampling. Instrumen yang digunakan berupa kuesioner minat dan pengetahuan yang telah melalui uji validitas dan reliabilitas. Analisis statistik menggunakan uji Paired t-test untuk variabel minat dan uji Wilcoxon untuk variabel pengetahuan dengan tingkat signifikansi α = 0,05. Hasil pretest menunjukkan sebagian besar responden berada pada kategori minat sedang (78,8%) dan pengetahuan sedang (62,5%). Setelah diberikan flashcard game, hampir seluruh responden menjadi kategori minat baik (61,3%) dan pengetahuan baik (78,8%). Nilai p 0,001 pada uji Wilcoxon dan p = 0,000 pada uji Paired T-test menunjukkan adanya perbedaan sebelum dan sesudah intervensi. Simpulan dari penelitian ini adalah flashcard game efektif dalam meningkatkan minat dan pengetahuan siswa sekolah dasar dalam menjaga kesehatan gigi Kata Kunci: Flashcard Game, Minat, Pengetahuan, Kesehatan Gigi, Sekolah Dasar.